Does health financial resource correlate with physical health infrastructure? - Motika Sinha Rymbai; Darishisha W.Thangkhiew (Indian Journal of Public Health, 2022)
The study attempts to examine the physical health infrastructure of northeastern states and public health resources.
Keywords: Accredited social health activists; Latent class analysis; Preterm birth; Low birth weight